2015
DOI: 10.1158/0008-5472.can-14-3121
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Identification of SEMA3F as an Antilymphangiogenic Metastasis Suppressor Gene in Head and Neck Squamous Carcinoma

Abstract: Head and neck squamous cell carcinomas (HNSCC) often metastasize to locoregional lymph nodes, and lymph node involvement represents one of the most important prognostic factors of poor clinical outcome. HNSCC are remarkably lymphangiogenic and represent a clear example of a cancer that utilizes the lymphatic vasculature for malignant dissemination; however, the molecular mechanisms underlying lymphangiogenesis in HNSCC is still poorly understood. Of interest, we found that an axon guidance molecule, Semaphorin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…Further endogeneous factors with anti-lymphangiogenic activity have been described, such as vasohibin [99], TGF-b [100] and semaphorins [101,102]. Interestingly, Tcells, respectively T-cell derived cytokines, have also emerged as inhibitors of lymphangiogenesis.…”
Section: Endogeneous Inhibitors Of Lymphangiogenesismentioning
confidence: 99%
“…Further endogeneous factors with anti-lymphangiogenic activity have been described, such as vasohibin [99], TGF-b [100] and semaphorins [101,102]. Interestingly, Tcells, respectively T-cell derived cytokines, have also emerged as inhibitors of lymphangiogenesis.…”
Section: Endogeneous Inhibitors Of Lymphangiogenesismentioning
confidence: 99%
“…60 Sema3F also functions as a potent inhibitor of lymphangiogenesis, a process that is critical for the metastatic spread of some types of solid tumors such as head and neck tumors or breast cancer tumors. 103,203 Recently it was suggested that sema3F may also be able to inhibit angiogenesis through competition with VEGF-A for binding to neuropilin-1, a receptor to which full length sema3F binds with low affinity as compared to its affinity to neuropilin-2 and which seems unable to convey sema3F signals. 100,204 However, cleavage with furin like pro-protein convertases at the sema3F C-terminus was found to result in an increase in its affinity to neuropilin-1 enabling it to compete effectively with VEGF-A for binding to neuropilin-1.…”
Section: 178mentioning
confidence: 99%
“…Plexins A1-A4 have been described as transducers of antiangiogenic signals conveyed by class-3 semaphorins such as sema3F, while the SEMA4D-PlexinB1 has been known as a potent inducer of angiogenesis and is associated with poor prognosis in various solid tumors (15,16). Angiogenesis and lymphangiogenesis intersect in the regulation of tumor microenvironment, and several recent studies also suggested that semaphorins may affect lymphangiogenesis (17,18). Nevertheless, the knowledge about the role of the semaphorin-mediated regulation of tumor lymphangiogenesis is still limited.…”
Section: Introductionmentioning
confidence: 99%